Bitury dam, in the Ipojuca river hydrographic basin, in the state of Pernambuco: approach in the light of water governance - Almeida, Jailson de Arruda; Valença, Sandro; Francisco, Iêdja Firmino da Silva; Santana, Poliana Nunes de; Vasconcelos, Erica Nunes (Revista de Administração da UFSM, 2024)
Purpose: The study proposes to analyse the water governance process of the Bitury weir, located in the Ipojuca river basin, in Pernambuco. Design/methodology/approach: A methodological approach with qualitative predominance was used, guided by comprehensive paradigms. It was an exploratory and descriptive case study, with the research corpus consisting of: (i) bibliographical and documentary research and (ii) semi-structured interviews. The Bitury weir, located in the hydrographic basin of the Ipojuca river, in Pernambuco, was adopted as a reference space for the research. The interviews were carried out with 10 subjects, from October 2020 to February 2021 and were treated through simplified content analysis — defined a priori and based on the OECD principles for water governance — were grouped into three dimensions: “effectiveness”, “efficiency” and “trust and commitment”. Findings: The roles and responsibilities of the management bodies are clear, however, the management practices are not compatible, in their entirety, with the local conditions of the hydrographic basin; the actors demonstrate to have technical skills and the data and information produced prove to be consistent, but the application of financial resources in the basin is deficient; and water allocation is carried out in the management of the weir, however, greater transparency and involvement of the actors is needed, as well as expanding inspection actions. Practical implications: Conception and implementation of public policies to face the challenges related to the management of water resources. Originality/value: The study contributes to the improvement of institutional models of water governance, based on knowledge of the water resources management model in force and the proposal for adjustments.